KESADARAN METAKOGNITIF MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR (PGSD) DI UNIVERSITAS QUALITY BERASTAGI - Johannes Keliat S.Pd. M.Pd; Dra Elisa M.Pd; Siska Moreta Br Sitepu (Universitas Quality, 2022)
To face the challenges of a globalized world requires Human Resources (HR) with potential. These challenges can be overcome if a person has good metacognitive potential. With good metacognition skills, it can overcome any problems in learning activities and in everyday life. Cognitive processes include changes that occur in individuals regarding thinking, intelligence and language. Metacognition refers to a person's skills in processing information and strategies in processing that information. In its implementation, metacognition is not as simple as its definition because it refers to a high-level mental process such as making plans, using appropriate strategies to solve a problem and making evaluation alternatives. Metacognition is an important aspect of individual learning. This includes self-regulation, reflection on strengths, weaknesses in self-performance and learning strategies. Based on this statement, metacognition plays a very important role in the learning activities of students in the primary school teacher education study program. through self-regulation activities, reflection on the weaknesses and strengths of what has been done and the learning strategies that have been pursued, students will be able to improve the quality of the process and learning outcomes. Research Objectives: To see the description of metacognition in students of the Elementary School Teacher Education Study Program (PGSD) at Quality Berastagi University. Research Method: Quantitative Descriptive using excel. The data obtained were analyzed using the Percentage Measurement Technique. Targeted outcomes: Students will get good metacognition. This research was conducted at the University of Quality Berastagi, North Sumatra with the research subjects being 258 students of the PGSD Study Program. The sampling technique was determined using a purposive sampling technique. The research instrument used the MAI (Metacognitive Awareness Inventory) questionnaire sheet which consisted of 52 questionnaire items consisting of 5 rating scales. Data analysis using quantitative descriptive using excel. The data obtained were analyzed by using the percentage measurement technique. The percentage of Metacognitive Awareness of PGSD Students reached 75.09%, the Percentage of Metacognitive Awareness Components of PGSD Students (Knowledge Abaout Cognition reached 25.03% & Regulation of Cognition reached 50.06%. Details of the Percentage of Metacognitive Awareness Components of PGSD Students (Declarative Knowledge (76%)) ), Procedural Knowledge (77.03%), Conditional Knowledge (77.08%), Planning (77.54%), Information Management Strategies (71.7%), Comprehension Monitoring (73.5%), Debugging Strategies ( 77%), and Evaluation (74.06%).